Willie Jennings on the Tongues of Pentecost: A Prophetic Messenger for Pentecostals - Mittelstadt, Martin William (2025)
The author attends primarily to Willie Jennings’ reading of Pentecost described in his commentary on Acts and other publications. The author crafts his response around major themes critical to Pentecostal readers. He expresses his belief that Jennings is a prophet. Pentecostal scholars and pastors need to hear Acts according to Jennings, specifically, that the Spirit released on the Day of Pentecost sets in motion the tale of a relentless and loving God.
Keywords: prophethood; Pentecost; Tongues; Acts; Willie James Jennings